Wie denken Lehramtsstudierende über Mathematikaufgaben? : Ein methodischer Ansatz zur Erfassung subjektiver Theorien mittels Repertory-Grid-Technik (mathematica didactica, 2003)
The article presents a method to explore subjective theories about mathematical problems by using the repertory grid technique. It has been developed in order to document individual levels of language and reflection about mathematical problems. On this basis, we can describe individual learning effects in teacher education courses. We first used the repertory grid method for the qualitative evaluation of a preservice teacher student course. The article discusses three case studies of the evaluation project.